The Use of Hanseniaspora opuntiae to Improve ‘Sideritis’ Wine Quality, a Late-Ripening Greek Grape Variety - Maria-Evangelia Filippousi; Ioanna Chalvantzi; Athanasios Mallouchos; Ioannis Marmaras; Georgios Banilas; Aspasia Nisiotou (Foods, 2024)
In view of climate change and the increasingly antagonistic wine market, the exploitation of native genetic resources is revisited in relation to sustainable wine production. ‘Sideritis’ is a late-ripening Greek grape variety, which is quite promising for counteracting wine quality issues associated with the annual temperature rise. The aim of this study was to improve the quality and to enhance the aroma of ‘Sideritis’ wine through the use of native yeasts. To improve vinification, Hanseniaspora opuntiae L1 was used along with Saccharomyces cerevisiae W7 in mixed fermentations (SQ). The addition of H. οpuntiae significantly altered the chemical profile of the wine compared to the single-inoculated fermentations with W7 (IS). H. opuntiae increased all the acetate esters, except for hexyl acetate and (Z)-3-hexen-1-ol acetate. The concentration of 2-phenylethyl acetate, which imparts flowery and sweet notes, exhibited a 2.6-fold increase in SQ as compared to IS wines. SQ also showed higher levels in several ethyl esters, including ethyl butyrate, ethyl heptanoate and ethyl 7-octenoate, which are associated with fruity notes compared to IS. H. opuntiae produced citronellol, a terpene associated with rose and green notes, and increased the overall acceptance of the wine. Present results are thus quite promising for improving ‘Sideritis’ wine quality towards a sustainable wine production in Greece in view of global warming.